Heeding the Call : A Study of Denise Giardina's Novels - Jolliff, William (Book collections on Project MUSE., 2020)
"In Heeding the Call, William Jolliff offers the first book-length discussion of West Virginia writer and activist Denise Giardina, perhaps best known for her novel Storming Heaven, which helped spark renewed interest in the turn-of-the-century Mine Wars. Jolliff proposes that Giardina's fiction be considered under three thematic complexes: regional, political, and theological"--